(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Enzyme engineering has emerged as a pivotal technology in the food industry, offering novel solutions to enhance food processing, preservation, and nutritional quality. This study delves into the multifaceted role of enzyme engineering within food technology, aiming to elucidate its impact on developing sustainable, efficient, and consumer-friendly food products.